2011
DOI: 10.1038/ismej.2011.99
|View full text |Cite
|
Sign up to set email alerts
|

The phylogenetic composition and structure of soil microbial communities shifts in response to elevated carbon dioxide

Abstract: One of the major factors associated with global change is the ever-increasing concentration of atmospheric CO2. Although the stimulating effects of elevated CO2 (eCO2) on plant growth and primary productivity have been established, its impacts on the diversity and function of soil microbial communities are poorly understood. In this study, phylogenetic microarrays (PhyloChip) were used to comprehensively survey the richness, composition and structure of soil microbial communities in a grassland experiment subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 90 publications
(110 reference statements)
8
72
1
1
Order By: Relevance
“…As consequences, increased carbon input in turn significantly changed bacterial diversity, composition, and structure and increased the functional potential of bacterial communities for carbon degradation and nutrient cycling, although such effects differed across various ecosystems (6,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In contrast, fungal biomass and relative abundance of total microbial biomass did not change significantly under eCO 2 in this BioCON (biodiversity, CO 2 , and N deposition) experimental site (6,21).…”
mentioning
confidence: 72%
“…As consequences, increased carbon input in turn significantly changed bacterial diversity, composition, and structure and increased the functional potential of bacterial communities for carbon degradation and nutrient cycling, although such effects differed across various ecosystems (6,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In contrast, fungal biomass and relative abundance of total microbial biomass did not change significantly under eCO 2 in this BioCON (biodiversity, CO 2 , and N deposition) experimental site (6,21).…”
mentioning
confidence: 72%
“…Several previous studies showed that the microbial community composition and structure was affected by eCO 2 (Feng et al, 2010;He et al, 2010bHe et al, , 2012bDeng et al, 2012;Hayden et al, 2012), eO 3 and/or eCO 2 þ eO 3 (Phillips et al, 2002;Kasurinen et al, 2005;Kanerva et al, 2008). For example, a previous study at the BioCON site showed that eCO 2 increased plant and microbial biomass, soil pH and moisture and significantly shifted the functional and phylogentic/taxonmoic composition, structure and network interactions of soil micorbial communities (Zhou et al, 2010;He et al, 2010bHe et al, , 2012bZhou et al, 2011;Deng et al, 2012). In this study, the results support this hypothesis demonstrated by adonis and Detrended correspondence analysis analyses of all detected functional genes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, no detectable effects of eCO 2 on microbial community structure, microbial activity, potential soil N mineralization or nitrification were observed at a sweetgum free-air CO 2 enrichment (FACE) experiment in TN, USA (Austin et al, 2009), whereas in a no-till wheat-soybean rotation agro-ecosystem, the community composition and structure significantly affected by eCO 2 but not by eO 3 or eCO 2 þ eO 3 (Cheng et al, 2011). Recently, more studies suggest that eCO 2 and/or eO 3 significantly alter microbial community composition, structure, functional potential/activity, interaction network and/or dynamics (Lesaulnier et al, 2008;Blagodatskaya et al, 2010;Drigo et al, 2010;Feng et al, 2010;Zhou et al, 2010Zhou et al, , 2011He et al, 2010bHe et al, , 2012bDeng et al, 2012;Drigo et al, 2013;Li et al, 2013). In addition, it has been shown that the response of soil microbial comunities to global change factors may be directly or indirectly mediated by plant genotypes/cultivars, the diversity of plant assemblages and/or other environmental factors (Talhelm et al, 2009;Singh et al, 2010;Drigo et al, 2013;Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Any significance levels lower than 0.05 were chosen (50). Mantel tests were performed to assess any correlation between AOA and AOB community structures and the measured environmental variables (51). The measured environmental variables were first normalized to zero means and unit standard deviations.…”
Section: Figmentioning
confidence: 99%